POLITICAL PARTIES OF KAZAKHSTAN IN THE 2005 ELECTION CAMPAIGN: ESSONS, CONCLUSIONS,AND PROSPECTS - DIACHENKO, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2006)
Today, with the democratic reforms moving ahead, with domestic political stability due to an effective presidency, and with clear prospects for the country’s social and economic development, the problem of sociopolitical consolidation has come to the fore, while political parties are tending to integrate into larger units.In democratic countries, the political parties involved in various ways in state administration have an important role to play in shaping the power system. This stirs civil society into action, which, in turn, contributes to the way key sociopolitical issues are resolved. At the same time, it is commonly believed that elections are the main focal point of the political parties’ activities: by their very nature they are designed to win state power and govern the state. The parties are expected to consolidate society and to shape public moods in a constructive way to avoid social disintegration at the most trying and far from easy times, such as presidential elections. For obvious reasons, different political parties use different instruments to influence electoral preferences.Kazakhstan is moving ahead along the road of democracy and democratic traditions; its party system has already covered a short, yet dynamic stretch of this road filled with all kinds of transformations. The parties have already left the initial development stages behind; they have withstood the test of several election campaigns and found their own niche in the republic’s sociopolitical hierarchy. The country has already passed the time when the political parties operating on the domestic political scene could not be described as a party system.1 It is commonly and correctly believed that at the earlier stages of party development, society mistrusted the new structures that overused bombastic declarations, unfeasible promises, and the administrative resource.Indeed, the new state’s first decade was a kaleidoscope of all sorts of political structures that appeared, split, disappeared, or merged before the nation’s eyes.Since that time the party system has obviously advanced much further.2 All political forces are involved in a competition that calls for concrete and practical steps and rejects the use of the administrative resource and coercion. On the one hand, the party system has not yet acquired its final shape; on the other, the gradually unfolding political liberalization helps parties and public movements join the political-power processes underway in the republic.In the last few years, Kazakhstan has finally established the “rules of the political game,” which allowed most of the political parties to acquire their social bases, electoral, and even parliamentary history. Today, the parties do not limit themselves to elections—they also want to have a say in creating the rules of the election procedure.3 We can agree with those who say that today the role of the political parties in an uncompromising and public power struggle is higher than ever.4 Life has shown that some of the players proved unequal to the heat of the inter-party race.Systemic democratization of the country’s political field led to the emergence of serious political forces—large parties able to affect the political context across the republic. The changes in the republic’s electoral legislation the parliament adopted made it possible to treat the formation and functioning of the political parties more seriously. On the other hand, the state needs a strong and stable multiparty system that would let it address problems in different ways and stimulate the country’s political developments.